Relations Between Parental Emotion Talk and Preschoolers’ Emotion Expressions in Low-Income Chinese American and Mexican American Families - Megan Chan; Michelle Taw; Nancy Eisenberg; Qing Zhou (Children)
Background/Objectives: Preschool children learn to express emotions in accordance with sociocultural norms. Parental emotion talk (ET) has been theorized to shape these processes. Limited research has examined preschoolers’ observed emotion expressions and emotion-related behaviors in culturally diverse samples. We sought to explore the following: (1) cultural group differences and similarities in observed emotion expressions (anger, sadness, and positive emotions) and emotion-related behaviors between Chinese American and Mexican American preschoolers, and (2) the concurrent links between parental ET and children’s emotion expressions. Methods: In a sample of 86 children (age range = 38 to 70 months, 62% girls) from low-income immigrant families (Mexican Americans/MA = 43 and Chinese Americans/CA = 43), the observed children’s emotion expressions and emotion-related behaviors were coded based on a frustration-eliciting task. Parental ET quality and quantity were coded from transcripts of a parent–child shared reading task. Results: MA children expressed more anger and sadness, but the two groups did not differ on positive emotions or emotion-related behaviors. Multiple regressions showed that children whose parents engaged in more ET expressed higher levels of anger and sadness and used more non-feeling state languages than children whose parents engaged in less ET. Conclusions: The results revealed cultural variations in preschool-age children’s emotion expressions and provided support for associations between parental ET and children’s emotion expressions.